Carbon depth profile and internal stress by thermal energy variation in carbon‐doped TiZrN coating. Issue 1 (21st September 2020) - Hong, Eunpyo; Kim, Taewoo; Kim, Seonghoon; Lee, Seon‐Hong; Lee, Heesoo
Abstract: Diffusion and bonding behavior of the doped carbon by variation of thermal energy was investigated in terms of carbon depth profile and local atomic structure. The thermal energy of pulsed laser was limited to the range of 20% 50% to dope the carbon and prevent degradation of the coating layer with laser carburization. The doped carbon was confirmed to be distributed to a depth of around 20 nm from the surface at 20% thermal energy by ToF‐SIMS analysis. Carbon diffused at about 400 nm with 50% thermal energy, and most of the carbon spread from the surface to around 80 nm. The EXAFS analysis represented that the peak of the interstitial carbon site was formed at 20% and the ZrN peak shifted toward the ZrC peak by increasing the thermal energy. The analysis of the electronic structure and the bonding state demonstrated that the proportion of substitutional carbon was about 21% at a thermal energy of 50%. The internal stress was calculated using HR‐XRD with a 5‐axes sample stage, which was −453 MPa before doping and then increased to −1494 MPa at 50% because the mixture of interstitial and substitutional carbon increased distortion inside the coating layer. The elastic modulus and hardness were 459 and 37.9 GPa at 50%, respectively, which were improved by 10% and 20% compared to those of the TiZrN coating.